2010
DOI: 10.1136/thx.2009.122002
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in COPD: are women more susceptible to smoking effects than men?

Abstract: BackgroundThe number of female smokers developing chronic obstructive pulmonary disease (COPD) is rapidly increasing, but whether or not there exists a differential susceptibility by gender remains controversial. Methods How smoking behaviour and subsequent lung function reduction differed by gender was examined in a study including 954 subjects with COPD and 955 subjects without COPD. The study focused on two subgroups: subjects with COPD <60 years of age (earlyonset group, n¼316) and subjects with COPD with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
198
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(228 citation statements)
references
References 31 publications
15
198
3
7
Order By: Relevance
“…Women are known to be more susceptible to developing COPD [29] and have less declining COPD-related mortality rates than men [30], but factors influencing sex differences in treatment are still an understudied area. Women have been reported to have more symptoms and more exacerbations in COPD [31], but as our analyses adjusted for both CAT and CCQ scores and for previous frequent exacerbations, difference in these factors should not explain the increased medication in women in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Women are known to be more susceptible to developing COPD [29] and have less declining COPD-related mortality rates than men [30], but factors influencing sex differences in treatment are still an understudied area. Women have been reported to have more symptoms and more exacerbations in COPD [31], but as our analyses adjusted for both CAT and CCQ scores and for previous frequent exacerbations, difference in these factors should not explain the increased medication in women in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…10 The diagnosis of COPD in females increased in the United Kingdom as well as Canada, whereas rates of diagnosis have plateaued in males. 14,15 Recent studies have shown more severe disease than previously noted in both smokers and nonsmokers with a substantial prevalence (3%-11%) in life-long nonsmokers, most likely related to nontobacco environmental exposures or infectious etiologies. 16 As noted, COPD is under diagnosed and may be related to patients failing to recognize early symptoms and restrict activities to avoid symptoms.…”
Section: Prevalencementioning
confidence: 91%
“…About 85-90% of cases of this disorder are due to tobacco consumption. Around 15-20% of smokers can develop COPD during their lifetime [1,2].…”
Section: Introductionmentioning
confidence: 99%